2021
DOI: 10.21037/tlcr-21-165
|View full text |Cite
|
Sign up to set email alerts
|

The clinical impact of three validated PD-L1 immunohistochemistry assays as a prognostic factor in small cell lung cancer

Abstract: Background: Evidence of the clinical impact of programmed death-ligand 1 (PD-L1) expression in small cell lung cancer (SCLC) is scarce and conflicting, even though atezolizumab became the first PD-L1 inhibitor approved by the US Food and Drug Administration (FDA) in recent years for the initial treatment of extensive-stage (ES)-SCLC.Methods: We investigated PD-L1 expression in SCLC tumors using the three validated PD-L1 immunohistochemistry (IHC) assays (SP263, SP142, and 22C3) and assessed the correlation bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 38 publications
(63 reference statements)
1
9
0
Order By: Relevance
“…We found that the prognostic value of the SII is superior to the values of the other CBC-IBs (NLR, PLR, and MLR) in ES-SCLC. Similar to our previous finding [ 22 ], SP142 expression was significantly associated with a longer OS in patients with ES-SCLC. Furthermore, the combined SII-SP142 biomarker was better for predicting both survival and progression in patients with ES-SCLC.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We found that the prognostic value of the SII is superior to the values of the other CBC-IBs (NLR, PLR, and MLR) in ES-SCLC. Similar to our previous finding [ 22 ], SP142 expression was significantly associated with a longer OS in patients with ES-SCLC. Furthermore, the combined SII-SP142 biomarker was better for predicting both survival and progression in patients with ES-SCLC.…”
Section: Discussionsupporting
confidence: 91%
“…To evaluate the PD-L1 expression, we used the widely used validated VENTANA PD-L1 SP142 IHC assay (Ventana Medical Systems, Inc., Tucson, AZ, USA), as previously described [ 22 ]. The PD-L1 expression in the immune cells (IC) and tumor (TC) cells was assessed in formalin-fixed paraffin-embedded tumor samples obtained via tissue biopsy at diagnosis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some retrospective studies showed that the expression of PD-L1 was significantly higher in early-stage SCLC than in extended disease (p = 0.011), and resulted in an independent prognostic biomarker of a favorable outcome [62][63][64]. In contrast, some studies of early stages of SCLC suggest that higher expressions of PDL-1 confer a worse prognostic in SCLC resected and that higher PDL1 expression is associated with a higher stage disease [65].…”
Section: Pd-l1mentioning
confidence: 99%
“…Several reasons are reported, including the different clones of antibodies used, the scoring systems, the type (resection or biopsy) of specimens evaluated, the cut-off values used, and the assessment of the PD-L1 staining pattern. A study of PD-L1 clinical impact assessment in advanced stage Acta Cytologica 2022;66:257-268 DOI: 10.1159/000519688 SCLC by ICC using the 3 approved antibodies was recently conducted by Lee et al [91]. Despite the positive correlation described between PD-L1 expression and a better patient outcome, the study has several limitations regarding the tissue determination, without a clear explanation of positivity assessment or cut-off or antibodies comparison description.…”
Section: Pd-l1 Expressionmentioning
confidence: 99%